Global Climate Change and Its Effects on Nature and Human Life;Evaluation of Vulnerability and Contributors to Climate Change (Global Journal of Sciences, 2024)
•  Climate change occurs as a result of the consistent alterations of the normal atmospheric weather conditions  that result in an imbalance of the earth’s climate, caused by the radiations from chemical, biological, or natural  sources, leading to an increased surface temperature that is capable of causing an intense threat to human's life,  plants, animals, and the planet ecosystem. The purpose of this study is to alert the world about the dangers  associated with climate change and the factors capable of causing climate change. This study also reveals the  top 10 countries that contribute the most to climate change through the emission of greenhouse gases and other  factors. Finally, this study will help to inform the world about the most vulnerable countries to climate change  in a ranking format from the most affected to the least. We used an MCDM technique called fuzzy preference  ranking organization method for enrichment evaluation (F-PROMETHEE) to rank the most vulnerable  countries to climate change. We considered 14 countries that have been severely affected by climate change,  and we evaluated them based on seven criteria. Results indicated that China is the highest contributor to climate  change as they emit (9,300 million tons) of greenhouse gases, followed by the USA (4,800 Mt), and Saudi Arabia  (532.2 Mt) occupies the tenth position as the countries that make this planet a risk zone for humans, plants,  and animals. Results from the PROMETHEE approach show that Mozambique is the most vulnerable country  to climate change, followed by India, and then Japan.
Keywords: Climate change; global warming; fuzzy-PROMETHEE; greenhouse gas